The Capitalist Economy and its Prosthetics - Wächter, Gerhard H. (transcript Verlag, 2024)
Notwithstanding its ruthless dynamics, the capitalist economy has the flaw of deficient employment-generating spending. This leads to unemployment of non-owners, individual suffering, social unrest and it undermines military strength. To deal with these issues, states use prosthetic policies, artificial transfers to the productive economy and to non-owners. But the funding of such prosthetic policies - through violent wealth appropriation abroad, protectionism, war, domestic expropriation and taxation, debt and money creation - is caught in dilemmas, while politicians are caught between non-solutions. According to Gerhard H. Wächter, the history of capitalist society is largely the history of this dilemmatic brotherhood.